Training leave : policies and practice in Europe - (:unkn) unknown (Publications Office of the European Union, 2012)
"The need for lifelong learning is leading to rising demand for training opportunities. This will involve a transformation of the learning environment within companies, but also the provision of training outside the job itself. For adult employees, some of the most important barriers to training are lack of time, and conflicting training and work schedules. Paid training leave can therefore encourage more adults to add to and upgrade their skills. In times of economic crisis, paid leave can also be combined with part-time work to alleviate the effects of decreased demand. With this study, Cedefop maps the application of training leave in Europe, reviews how it operates, analyses its performance in several countries (Austria, Belgium, Denmark, France, Hungary, the Netherlands, Poland and Spain), and sets out recommendations as to how to improve its effectiveness." (Hrsg. , BIBB-Doku)
Keywords: S 1.5.2 Berufliche Weiterbildung; I 2.2 Europa; Berufliche Weiterbildung; Weiterbildungsbeteiligung; Weiterbildungsförderung; Bildungsurlaub; Europa